Convert the evaluation into a learning opportunity.a suggestion for the spanish language course - Ana Blanco Canales (Universidad de La Rioja, 2013)
New methodologies of teaching developed in university classrooms demand urgent change in the systems of evaluation, because it is inexcusable that the evaluation is in the end, what determines what the students learn and how they learn. The formative integrated assessment presents, in moments, as a student platform with numerous possibilities for application. Interestingly, this generates multifuntional contexts for learning (acquisition of competencies, development of learning strategies, assessment of results, evaluation of the processes...), of which the participation and engagement of the student increases in a natural manner. With the objective to evaluate the effectiveness, the impact over the learning and its contribution to resolving some difficulties we have developed a proposal of global evaluation for the Spanish language course, which we describe with detail throughout this work. We present the supporting fundamentals, the objectives that follow it, the required methodology as well as the results obtained upon its implementation. Likewise, we offer the complete repertory of activities that make up the proposal, since with changes and simple adaptations, they can be useful to other professors.